Review on Tsunami Risk Reduction in Indonesia Based on Coastal and Settlement Typology - Djati Mardiatno; M. Ngainul Malawani; Dandun Wacono; Despry Nur Annisa (Indonesian Journal of Geography, 2017)
This research aims to identify various coastal and settlement typology as the basis to determine action plan for reducing tsunami risk. The action plan were issued by referring to priority level of tsunami management. Comparative analysis was applied through comparing different coastal and settlement typology at the selected coastal area, considering the tsunami risk zones determined by National Disaster Management Agency (BNPB). The results show that mitigation strategies can be distinguished in various coastal and settlement typology for each priority area, i.e. in Mentawai megathrust, Sunda Strait and the southern part of Java, Bali region and Nusa Tenggara, and Papua region. The components of action plan should be conducted in accordance with the priority level of each region.